Equality of Rights and Impact of Property in Mixed Marriage - Erni Rohaini; Toto Tohir Soeriatmadja; Lukman Ilman Nurhakim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to examine the rights equality and the impact of property in mixed marriages. The approach method used in this research is normative juridical, which is accomplished by conducting secondary data research on library materials, also known as library law research, using the Statute Approach, Conceptual Approach, and Historical Approach. According to the investigation's findings, the following are known: 1) Equal rights for mixed marriage partners are regulated in Articles 46 to 51 of Law No. 39 of 1999 concerning Human Rights, which regulates women's rights in the fields of politics, government, health, education and teaching, employment, citizenship, and the bond and dissolution of marriage, as well as the conduct of legal actions; and 2) Law No. 5 of 1969 concerning Agrarian Principles stipulates that A foreign national loses his or her Indonesian citizenship if, under the law of the husband's country of origin, the wife's citizenship automatically becomes the husband's as a result of the marriage